Biocontrol of Fusarium head blight in rice using Bacillus velezensis JCK-7158 - Yeo, Yu Jeong; Park, Ae Ran; Vuong, Bien Sy; Kim, Jin-Cheol (Frontiers in Microbiology, 2024)
Fusarium head blight (FHB) is a destructive disease caused by several species of Fusarium, such as F. graminearum and F. asiaticum. FHB affects cereal crops, including wheat, barley, and rice, worldwide. Fusarium-infected kernels not only cause reduced yields but also cause quality loss by producing mycotoxins, such as trichothecenes and zearalenone, which are toxic to animals and humans. For decades, chemical fungicides have been used to control FHB because of their convenience and high control efficacy. However, the prolonged use of chemical fungicides has caused adverse effects, including the emergence of drug resistance to pathogens and environmental pollution. Biological control is considered one of the most promising alternatives to chemicals and can be used for integrated management of FHB due to the rare possibility of environment pollution and reduced health risks. In this study, Bacillus velezensis JCK-7158 isolated from rice was selected as an ecofriendly alternative to chemical fungicides for the management of FHB. JCK-7158 produced the extracellular enzymes protease, chitinase, gelatinase, and cellulase; the plant growth hormone indole-3-acetic acid; and the 2,3-butanediol precursor acetoin. Moreover, JCK-7158 exhibited broad antagonistic activity against various phytopathogenic fungi and produced iturin A, surfactin, and volatile substances as active antifungal compounds. It also enhanced the expression of PR1, a known induced resistance marker gene, in transgenic Arabidopsis plants expressing β-glucuronidase (GUS) fused with the PR1 promoter. Under greenhouse conditions, treatments with the culture broth and suspension concentrate formulation of JCK-7158 at a 1,000-fold dilution inhibited the development of FHB by 50% and 66%, respectively. In a field experiment, treatment with the suspension concentrate formulation of JCK-7158 at a 1,000-fold dilution effectively controlled the development of FHB with a control value of 55% and reduced the production of the mycotoxin nivalenol by 40%. Interestingly, treatment with JCK-7158 enhanced the expression of plant defense-related genes in salicylic acid, jasmonic acid, ethylene, and reactive oxygen species (ROS) signaling pathways before and after FHB pathogen inoculation. Taken together, our findings support that JCK-7158 has the potential to serve as a new biocontrol agent for the management of FHB.